Molecular characterization of Hepatozoon sp in cats from Sao Luis Island, Maranhao, Northeastern Brazil - de Bortoli, Caroline P. [UNESP]; Andre, Marcos R. [UNESP]; Braga, Maria do Socorro C. [UNESP]; Machado, Rosangela Zacarias [UNESP] (Springer, 2011)
Few molecular studies have been done concerning the molecular characterization of Hepatozoon species among domestic and wild felids. The present work aimed to characterize molecularly the presence of Hepatozoon sp. DNA in cat blood samples from Sao Luis Island, Maranhao state, Northeastern Brazil. EDTA-whole blood samples were collected from 200 domestic cats with outdoor and wood areas access from Sao Luis, Maranhao, Brazil. Each sample of extracted DNA was used as a template in PCR reactions aiming to amplify a partial sequence of 18S rRNA of Hepatozoon spp. We also performed sequence alignment to establish the identity of the parasite species infecting these animals using DNA sequences based on 18S rRNA. From 200 sampled cats, Hepatozoon DNA was only found in one animal (0.5%). The found Hepatozoon DNA showed 97% of identity with Hemobartonella felis isolates 1 and 2 from Spain. When analyzing the phylogenetic tree, the found Hepatozoon DNA was in the same clade than H. felis isolates. Our findings suggest that more than one species of Hepatozoon could infect felids in Brazil.